Computer Aided Document Indexing System (CADIS) with Eurovoc - Dalbelo Bašić, Bojana; Tadić, Marko (2006)
Automatic indexing, text classification, text procesing, natural language processing, EUROVOC, Croatian, English
Projekt MZOS
ENG